Le caring thinking, au cœur des ambitions éthiques d’Ann Margaret Sharp : quelles recommandations concrètes dans l’accompagnement des vulnérabilités, au sein de la pratique philosophique avec les enfants ? - Johanna Hawken (Éducation et Socialisation)
While the works of Ann Margaret Sharp - american philosopher, and professor at the Montclair University from 1973 to 2010 - have often been placed in the shadow of Matthew Lipman, they offer us key elements to understand the building of philosophy for children since the 1970s. In particular, she has left a significant mark in regards to its ethical dimension. Notably, because of the influence of the thinkers of the ethics of care (Gilligan, 2008; Noddings, 1984; Tronto, 2009), she put forward the concept of caring thinking, which can be defined as an ethical mode of thinking oriented towards the other. The emergence of this concept is determined by a specific anthropological postulate: one in which humanity is defined by its vulnerability, its interdependence and its singularity. Indeed, the activity of caring thinking will be precisely centered on the support of these vulnerabilities that will arise during the collective dialogue. This article aims to analyze these moments where vulnerabilities appear: the sharing of ideas during the philosophical dialogue, the sharing of individual experiences and the emergence of emotions. What are Sharp’s pedagogical recommendations in order to support vulnerabilities? Are they sufficient?